2004
DOI: 10.1259/bjr/21985061
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting clinical outcome of patients who undergo transcatheter arterial embolisation in splenic injury

Abstract: Transcatheter arterial embolisation (TAE) offers a less invasive approach to traditional laparotomy for the management of bleeding in the context of blunt splenic injury. This is a retrospective review study to identify clinical factors associated with clinical outcome of the patients who underwent this procedure. Of 65 patients with splenic injuries at our institution, 26 patients underwent TAE for management of bleeding. The following factors were assessed to determine their relationship to procedure outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Increasingly adopted to manage traumatic splenic injuries, interventional treatment with transcatheter arterial embolisation (TAE) may also prove a valuable non-surgical option for ASR (Fig. 3 ), particularly in cases associated with anticoagulation, malaria, and mononucleosis, and when CT detects active arterial bleeding [ 2 , 17 , 27 , 28 ]. In selected patients, TAE is useful as a temporary stabilising measure.…”
mentioning
confidence: 99%
“…Increasingly adopted to manage traumatic splenic injuries, interventional treatment with transcatheter arterial embolisation (TAE) may also prove a valuable non-surgical option for ASR (Fig. 3 ), particularly in cases associated with anticoagulation, malaria, and mononucleosis, and when CT detects active arterial bleeding [ 2 , 17 , 27 , 28 ]. In selected patients, TAE is useful as a temporary stabilising measure.…”
mentioning
confidence: 99%
“…To our knowledge, this is the only case of ASR in the setting of CMML that has been treated with SAE. In general, SAE is well tolerated, with one study finding 73.1% of patients had a positive outcome with shorter hospital stays, fewer intensive care unit days, and fewer transfusions [9]. Although 8% of patients developed delayed complications (hemorrhage, splenic abscesses, and splenic pseudocysts), most patients did well [10].…”
Section: Discussionmentioning
confidence: 99%
“…Partial splenic artery embolization has been highly evaluated and recommended since the 1990s as the treatment of choice for hypersplenism, splenomegaly and hemorrhagic events (Shimizu et aI., 2003;OZdogo et al, 2004;Sekikawa et al, 2004). However, Sakai (2002), Inagawa et al (2004) and Moreno (2004) found that the most hazardous complication of this procedure was inadvertent passage of embolic material to the pancreatic branches of the splenic artery causing pancreatitis.…”
Section: Discussionmentioning
confidence: 99%